2012
DOI: 10.4236/ojvm.2012.24041
|View full text |Cite
|
Sign up to set email alerts
|

Canine Cutaneous Mast Cell Tumor: Biologic Behavior and Its Correlation with Prognostic Indicators

Abstract: Cutaneous mast cell tumor (MCT) shows a variable biological behavior in dogs and may present either as solitary masse that can be treated and cured with surgical removal or as a systemic metastatic and fatal disease. Histological grade, KIT pattern and proliferative index are typically prognostic factors in MCTs. In the present study, we have investigated correlation between clinical data (breed, age, gender, tumour location, tumor size, time before surgery, number of tumours, occurrence of metastasis and recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
1
0
5
Order By: Relevance
“…Estudos apontam que este tipo de neoplasia acomete mais os cães quando comparada a outras espécies de animais domésticos (Romansik et al, 2007). São várias as raças atingidas por mastocitoma, American Bully é uma delas, assim como outras mais semelhantes Pitbull, Bull Terrier, e que também podem ser comprovadas em diversos artigos (Costa-Casagrande et al, 2008;De Nardi et al, 2002;Dobson & Scase, 2007;Patnaik et al, 1984;Poggiani et al, 2012;Strefezzi et al, 2010;Welle et al, 2008). Há casos ainda em que até o porte do animal pode influenciar na incidência de tumores, como apresenta este estudo (White et al 2011), quanto maior o porte maior a chance de desenvolver a doença.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos apontam que este tipo de neoplasia acomete mais os cães quando comparada a outras espécies de animais domésticos (Romansik et al, 2007). São várias as raças atingidas por mastocitoma, American Bully é uma delas, assim como outras mais semelhantes Pitbull, Bull Terrier, e que também podem ser comprovadas em diversos artigos (Costa-Casagrande et al, 2008;De Nardi et al, 2002;Dobson & Scase, 2007;Patnaik et al, 1984;Poggiani et al, 2012;Strefezzi et al, 2010;Welle et al, 2008). Há casos ainda em que até o porte do animal pode influenciar na incidência de tumores, como apresenta este estudo (White et al 2011), quanto maior o porte maior a chance de desenvolver a doença.…”
Section: Discussionunclassified
“…Há casos ainda em que até o porte do animal pode influenciar na incidência de tumores, como apresenta este estudo (White et al 2011), quanto maior o porte maior a chance de desenvolver a doença. A idade é outro fator relevante como foi verificado em diversos artigos (Costa-Casagrande et al, 2008;De Nardi et al, 2002;Dobson & Scase, 2007;Patnaik et al, 1984;Poggiani et al, 2012;Strefezzi et al, 2010;Welle et al, 2008) em que a faixa etária classificada é de oito a nove anos. Outras pesquisas, como a descrita por Costa-Casagrande et al ( 2008) observaram incidência ainda maior em cães entre nove e 11 anos de idade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The expression of Ki-67 increases from G 1 phase, and reaches its peak level during the M phase (Scholzen and Gerdes 2000). Since many previous studies showed that Ki-67 is an accurate prognostic marker for MCT (Abadie et al 1999, Scase et al 2006, Webster et al 2007, Dos Santos Costa Poggiani et al 2012, we used its expression as a reference value for other analyzed proteins and histopathological grading systems. We showed that the expression of Ki-67 increased proportionally to the MCT grade.…”
Section: Discussionmentioning
confidence: 99%
“…As lesões de ceratose liquenóide que ocorrem na virilha e axilas devem ser diferenciadas dos papilomas de acantose e da dermatose psoriasiforme liquenóide. O aparecimento de lesões no pavilhão auricular pode auxiliar na diferenciação da ceratose liquenóide com essas enfermidades (Patnaik et al, 1984;Poggiani et al, 2012).…”
Section: Introductionunclassified